The Common between Malay Language and the Qur'an A model of curriculum for teaching Arabic to Malay speakers - Mahmoud Thabet Ibrahim (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2022)
AbstractThe Arabic language has a high position in the hearts of Muslims and their conscience, and there is no surprise in that; as it is the language of the holy Quran and the language of the noble hadith that the Noble Prophet uttered, and it is also the language of the honourable people of Paradise, and it is no wonder, then, that Muslims like learning the Arabic language. Study Problem: It is known that teaching Arabic to native speakers is different from the way it is taught to native speakers. It is also known that learning Arabic for Muslims is very important to master the recitation of the Holy Qur'an, and understand its secrets; so this study came to try to walk the way to teach Arabic and teach the Qur'an at the same time.   "Multiple statistics have shown that the majority of the main reasons behind the turnout of non-Arabic speakers depend on the desire to learn the language of the Qur'an."[1]   Study Methodology: In preparing this study, the researchers relied on the descriptive approach.  Objectives of the study:  This study aims to prepare a list of common vocabulary between Malay and Qur'anic words for use in building an integrated educational curriculum, to teach Arabic to Malay speakers.   Study Results: The results of this study show that the use of common vocabulary between Malay and Qur'anic words in building a curriculum to teach Arabic to Malay speakers, has implications for the development of students' language skills and the development of their trends towards the study of ArabicKeywords: common vocabulary list - Malay - language skills - non-native speakers - trends. [1] - Abdel-Ati, Muhammad Rajab, and Al-Khatib Muhammad. (2009). Technical employment of the Holy Quran in teaching Arabic to non-native speakers. Kingdom of Saudi Arabia, Medina: King Fahd Complex for Printing. p 1